Hypoglycemic Activity and Safety Assessment of Pediococcus acidilactici Strain DNH16 in Experimental Type 2 Diabetes Mellitus Rats Induced with Streptozotocin - Fachrial, Edy; Lina, Juliana; Harmileni, Harmileni; Anggraini, Sari; Sihotang, Widya Yanti (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Type 2 diabetes mellitus (T2DM) cases tend to rise throughout the year in all parts of the world. The α-glucosidase inhibitors are frequently used to both prevent and treat T2DM. This α-glucosidase inhibitor activity is seen in some probiotic species, and a certain strain of Pediococcus acidilactici exhibits promising characteristics as an α-glucosidase inhibitor. This study was conducted to assess the hypoglycemic activity and safety of P. acidilactici strain DNH16 (PADNH16) in experimental rats with T2DM induced by streptozotocin.METHODS: The experiment was conducted in vivo using Wistar rats. Acarbose was employed as a positive control, and Lactobacillus casei was used as a comparative. For 24 days, post-prandial blood glucose levels were assessed every 3 days, followed by serum biochemical levels measurement of liver, kidney, and lipid profiles. The pancreas was histopathologically examined utilizing the Hematoxyline-Eosin staining procedure.RESULTS: Administration of PADNH16 to T2DM rats lowered post-prandial blood glucose levels and gave hypoglycemic benefits comparable to acarbose and commercial probiotics. PADNH16 dosing did not affect serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), urea, or creatinine levels, showing that PADNH16 was not hazardous to liver or kidney function. The lipid profile assessment revealed that the values, including high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides, were comparable to the control group. The pancreatic histopathology revealed that injection of PADNH16 caused no alterations to pancreatic β cells.CONCLUSION: P. acidilactici isolate DNH16 has a hypoglycemic effect on T2DM rats, but does not affect liver function enzymes, kidneys, lipid profiles and does not provide significant changes in pancreatic β cells.KEYWORDS: diabetes mellitus, inhibitor α-glucosidase, Pediococcus acidilactici strain DNH16